Respuesta :

Answer:

-1 / x + (x + 1) / (x² + 3)

Step-by-step explanation:

(x − 3) / (x (x² + 3))

There are two factors in the denominator, so split this into two fractions with unknown numerators:

A / x + (Bx + C) / (x² + 3)

Combine back into one fraction:

(A (x² + 3) + (Bx + C) x) / (x (x² + 3))

Now equate this numerator with the original:

A (x² + 3) + (Bx + C) x = x − 3

Ax² + 3A + Bx² + Cx = x − 3

(A + B) x² + Cx + 3A = x − 3

Match the coefficients:

A + B = 0

C = 1

3A = -3

Solve:

A = -1

B = 1

C = 1

Therefore, the partial fraction decomposition is:

-1 / x + (x + 1) / (x² + 3)

Here's a graph showing that the two are the same:

desmos.com/calculator/hrxfnijewh

ACCESS MORE